Hybrid Generation Power System for Domestic Applications - Qazi Waqar Ali; Muhammad Aamir; Arshad Nawaz; Zaki Udin; Shahid Ullah (Institute of Advanced Engineering and Science, 2014)
This work presents the plan and model of the control strategy for the interconnection of the hybrid energy system able to regulating this load’s voltage and controlling the energy generation with the energy options. The control strategy contains controlling the energy generated through each energy source, in a hierarchical mode using sliding/dropping mode control, while consuming consideration elements that have an impact on each electrical power source and transform the energy generated in order to suitable circumstances for lower power and domestic programs. The cross alternative energy system consists of photovoltaic cellular material, fuel cellular material and battery packs. A numerical equation in order to estimate the perfect voltage involving photovoltaic systems for virtually every solar irradiance and temperature circumstances is suggested. Simulations of a single or a lot more systems interconnected towards the load with the entire proposed control scheme, under different ecological and weight conditions, usually are introduced to indicate this efficiency with the procedure.